Acid-Suppressive Drugs and Risk of Fracture in Children and Young Adults: A Meta-Analysis of Observational Studies - Li, Jiangbi; Xie, Xiaoping; Liu, Weibing; Gu, Feng; Zhang, Ke; Su, Zilong; Wen, Qiangqiang; Sui, Zhenjiang; Zhou, Pengcheng; Yu, Tiecheng (Frontiers in Pharmacology, 2021)
Background: Recent studies have suggested an increased risk of fractures with proton pump inhibitors (PPIs) and histamine-2 receptor antagonists (H2RAs). We planned to perform a meta-analysis of fractures in young and children taking PPIs and H2RAs. Methods: PubMed, EMBASE databases, Cochrane Library and Web of Science for relevant articles published before May 2021 were searched. All controlled observational studies that reporting on the risk of fractures with acid-suppressing medication (PPIs and H2RAs) in young and children were included We combined odds risks (ORs) for fractures using random-effects models and conducted subgroup and stratified analyses. Results: A total of six studies were included in our meta-analysis. Pooled analysis of PPIs use showed significant risk for fractures in a random-effects model meta-analysis (OR = 1.23; 95% CI, 1.12-1.34; I2 = 79.3%), as well as PPIs and H2RAs (OR = 1.22; 95% CI, 0.94-1.60; I2 = 79.3%), but this was not significant for H2RAs (OR = 1.08; 95% CI, 0.94-1.24; I2 = 84.1%). In addition, the use of PPIs or H2RAs increased the risk of fracture more significantly in case-control study, compared to cohort studies. Grouping of studies by country showed a significantly increased fracture risk with PPIs use in USA studies (OR = 1.24; 95% CI, 1.16-1.32; I2 =0.0%) and other country studies (OR = 1.20; 95% CI, 1.01-1.41; I2 = 89.2%). However, there was no association between H2RAs use and fracture risk in USA studies (OR = 1.08; 95% CI, 1.00-1.09; I2 = 0.0%). Conclusions: PPIs or with H2RAs use could increase the risk of fractures in young and children, but not H2RAs, clinicians should carefully consider their decision to prescribe PPIs for patients.